Team characteristics associated with weight loss in a First Nations community intervention: An observational study. Issue 1 (4th October 2022) - Bohn‐Goldbaum, Erika; Cashmore, Aaron; Bauman, Adrian; Sullivan, Anna; Fonua, Lose (Rose); Milat, Andrew; Reid, Kate; Grunseit, Anne
Abstract: Issue addressed: Group‐based weight‐loss programs can be effective in addressing high rates of overweight and obesity among Aboriginal and Torres Strait Islander Peoples. The purpose was to determine associations between demographic and baseline weight‐related variables and team weight loss in a community‐based intervention as no previous studies have analysed this at a team level. Methods: Binomial models tested associations between team‐level age, proportion female and baseline weight and classification as higher weight‐loss team (HWT) (>50% persons losing 2.5% of initial weight) vs lower weight‐loss team (LWT). Linear regressions compared HWT and LWT on diet and physical activity (PA) outcomes adjusted for age and gender. Results: For each 1 kg increment in mean baseline weight, a team's likelihood of higher weight loss was increased by 4% (APR: 1.04, 95%CI: 1.00, 1.08). HWTs increased vigorous PA by 0.32 sessions more than LWTs ( P = .02). Fruit and vegetable intakes were not associated with team weight loss classification. Conclusions: Only baseline weight and vigorous PA distinguished HWT and LWT. Promoting PA components in team‐based weight‐loss approaches may be beneficial as these lend themselves to group participation. So what?: Demographic and baseline weight‐related variables are largely not predictive of weight loss success in group programs. Identifying other characteristics shared by HWT may help teams achieve weight loss.